إدارة الخراج في كتاب الخراج لأبي يوسف وكتاب الأحكام السلطانية لأبي يعلى الفراء - Rosmita Rosmita; Riska Riska; Andi Indra Puteri; Linka Anastasya Monoarfa (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This research discusses the management of Kharāj in the book al-Kharāj by Abū Yūsuf and the kitāb al-Ahkām al-Sulṭāniyya by Abū Ya'lā. The aim of the research is to find out the management of Kharāj in the book al-Kharāj by Abū Yūsuf, to know the management of Kharāj in the book al-Ahkām al-Sulṭāniyya by Abū Ya'lā, and to find out the similarities and differences in views between Abū Yūsuf and Abū Ya'lā in management Kharaj. The research methods used to achieve the objectives are deductive, inductive, and comparative methods. The research results show several things. First, kharaj according to Abū Yūsuf is what is properly taken from the property of those who fight the Muslims without resorting to violence. The Kharaj collection system that he implemented was a profit-sharing system. Second, according to Abū Ya'lā, kharaj is what is imposed on the land owner in the form of rights that must be fulfilled on the land, and the collection system applied has three methods: based on the size of the land, the size of the land planted, and the percentage of production. Third, the similarity in views between Abū Yūsuf and Abū Ya'lā is that both of them agree with Jumhur regarding the meaning of Kharāj, the property taken from Kharāj, the land where Kharāj is located, its distribution system, and its managers. The difference is in the collection system and kharaj percentage.